2020
DOI: 10.1016/j.toxrep.2020.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity of mixture of imidacloprid, imazalil and tebuconazole

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 43 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…Agricultural soils and even public playgrounds are frequently contaminated by pesticide mixtures [ 38 ]. Pesticides can have greater toxic effects in mixtures than when they are tested individually in earthworms [ 39 ] and other animal species such as chicks [ 40 ], salmon [ 41 ] or on mammalian bone marrow erythrocytes in CD-1 mice [ 42 ]. Recent scientific studies have highlighted the need to test real-life exposure scenarios [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Agricultural soils and even public playgrounds are frequently contaminated by pesticide mixtures [ 38 ]. Pesticides can have greater toxic effects in mixtures than when they are tested individually in earthworms [ 39 ] and other animal species such as chicks [ 40 ], salmon [ 41 ] or on mammalian bone marrow erythrocytes in CD-1 mice [ 42 ]. Recent scientific studies have highlighted the need to test real-life exposure scenarios [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…by using a metabolically active cell line like HepG2 cells or bioactivation by S9 mix. Effects of mixtures of chemicals may show different effects than substances alone, even at very low doses [ 30 , 31 ]. As this may also occur when celecoxib is administered along with other pharmaceuticals, a comprehensive genotoxicity assessment should also consider combination effects.…”
Section: Resultsmentioning
confidence: 99%
“…The Micronucleus assay is used for evaluation of the potential mutagenic activity of new substances in order to classify them by mutagenic hazard, besides is highly efficient as an indicator of induced chromosomal lesions for the substances tested [ 35 ], additionally the evaluation of mixtures like the ones found in extracts, it has to be tested because is clear that mixtures can induce genotoxic effects even if each of the compounds separately does not manifest such activity in testing. Therefore, it is necessary to evaluate the genotoxicity of herbal drugs to ensure the safety of patients who take these products [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are safety reports for the consumption of C. spinosa gum that were reported in 2012 for the evaluation of Galactomannans of the plant in cosmetics. In this report it was shown that the gum does not show toxic effects (acute and chronic toxicity at 90 days), as well as being non-irritating and non-teratogenic [ 20 , 21 , [35] , [36] , [37] ]. Polyphenol extracts like the Yukmijihwang-tang, an herbal formula used for kidney ailments such as pollakisuria (urination at short intervals) and edema, showed that is not genotoxic at the proper dose [ 33 ].…”
Section: Discussionmentioning
confidence: 99%